K(2P)2.1 (TREK-1) potassium channel activation protects against hyperoxia-induced lung injury - Zyrianova, Tatiana (Sci Rep, 2020)
No targeted therapies exist to counteract Hyperoxia (HO)-induced Acute Lung Injury (HALI). We previously found that HO downregulates alveolar K(2P)2.1 (TREK-1) K(+) channels, which results in worsening lung injury. This decrease in TREK-1 levels leaves a subset of channels amendable to pharmacological intervention. Therefore, we hypothesized that TREK-1 activation protects against HALI. We treated HO-exposed mice and primary alveolar epithelial cells (AECs) with the novel TREK-1 activators ML335 and BL1249, and quantified physiological, histological, and biochemical lung injury markers. We determined the effects of these drugs on epithelial TREK-1 currents, plasma membrane potential (Em), and intracellular Ca(2+) (iCa) concentrations using fluorometric assays, and blocked voltage-gated Ca(2+) channels (Ca(V)) as a downstream mechanism of cytokine secretion. Once-daily, intra-tracheal injections of HO-exposed mice with ML335 or BL1249 improved lung compliance, histological lung injury scores, broncho-alveolar lavage protein levels and cell counts, and IL-6 and IP-10 concentrations. TREK-1 activation also decreased IL-6, IP-10, and CCL-2 secretion from primary AECs. Mechanistically, ML335 and BL1249 induced TREK-1 currents in AECs, counteracted HO-induced cell depolarization, and lowered iCa(2+) concentrations. In addition, CCL-2 secretion was decreased after L-type Ca(V) inhibition. Therefore, Em stabilization with TREK-1 activators may represent a novel approach to counteract HALI.